Exploring omentin-1 gene expression and insulin-resistance modulation in diabetic and obese male albino rats - Al-Sowayan, Noorah Saleh; Almutawa, Aiesha Mohammed (Intelektual Pustaka Media Utama, 2025)
Omentin-1, a cytokine secreted by adipose tissue, plays a role in metabolic regulation and insulin sensitivity. However, there is a lack of understanding about the specific effects of high-intensity training (HIT) in diabetic and obese individuals. The present study investigates the effect of a 5-week HIT program on the omentin-1 gene expression and insulin resistance in diabetic and obese male albino rats. Thirty-two rats weighing between 100-120 grams, were procured and divided into groups: the control group (receiving a normal diet), the high-fat diet group (non-diabetic obese rats), the HIT diabetic group (induced diabetes through streptozotocin administration and subjected to HIT), and the diabetic control group (induced diabetes but not subjected to HIT). The HIT diabetic and HIT obese groups underwent a 5-week HIT protocol, involving treadmill running for 60 minutes at 34 m/min speed, five sessions per week. At the end of the experiment, various parameters including glucose, insulin, insulin resistance, LDL, HDL, TC, TG levels, and omentin-1 gene expression assessed using samples obtained from visceral tissue. SPSS version 25 was used to perform statistical analysis, results as mean±SE. One-way ANOVA identified group differences, with significance level (p-value) of less than 0.05. The findings revealed that omentin-1 gene expression significantly increased in the HIT diabetic group following five weeks of training. Both training groups exhibited reductions in insulin, glucose, and insulin resistance levels. It is concluded that a 5-week HIT program can lead to enhanced omentin-1 gene expression and improved insulin resistance in diabetic and obese male albino rats.